Earthquake-Resistant Design of Steel Frames with Intentionally Eccentric Braces - González Ureña, Andrés (2021)
Braces with Intentional Eccentricity (BIEs) have been proposed to overcome some of the shortcomings of Concentrically Braced Frames (CBFs), namely the implications of their inherently stiff nature, their limited post-yielding stiffness and the susceptibility of Hollow Structural Sections (HSSs) to premature local buckling and fracture, and the excessive overstrength that may result from the design codes limits on the local and global slenderness. However, the application of BIEs for use in buildings has not yet been attempted, nor has their implementation in a global design approach yet been addressed. In this paper, a procedure based on the Direct Displacement Based Design (DDBD) method is employed in the seismic design of Frames with Intentionally Eccentric Braces (FIEBs). Buildings of 4, 8 and 12 storeys are designed as FIEBs with HSS brace members, with target drift ratios of 1.5% and 2.5%, and as Special CBFs for comparison purposes. The performance of the resulting buildings is assessed through Non-Linear Response-History Analysis. The results show that the employed design procedure is well suited to FIEBs, that their seismic performance is satisfactory and complies with the proposed performance objectives, and that they can constitute an economically advantageous alternative to conventional CBFs.